Investigating the Impact of Profitability on Bankruptcy Risk in Cosmetic Manufacturing Firms - Nita Yura Roslina (Majalah Bisnis & IPTEK, 2026)
This study aims to analyze the effect of profitability ratios, namely Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), and Net Profit Margin (NPM), on corporate bankruptcy prediction using the Altman Z-Score model. The sample consists of five cosmetic manufacturing companies listed on the Indonesia Stock Exchange during 2019–2024 (30 observations). The research employs a quantitative approach using multiple linear regression analysis. The results indicate that profitability ratios simultaneously have a significant effect on Z-Score (R² = 0.607; Sig = 0.000). Partially, only NPM significantly affects bankruptcy prediction, while ROA, ROE, and GPM are not significant due to multicollinearity issues. The findings highlight that net profit is the most sensitive indicator in detecting financial distress risk. This study contributes empirically to bankruptcy prediction modeling in the Indonesian manufacturing sector.